Experimental Investigation of Annular Flow Behaviour in Horizontal Pipe - Osokogwu; Uche (International Journal of Integrated Engineering, 2021)
The experimental investigations of annular flow were conducted in horizontal pipe using water/air in a 0.0504m internal diameter pipe loop with a total length of 28.68m. To understand annular flow behaviors, conductivity ring sensors, conductance probe sensors and Olympia high speed digital camera were used. In all the experiments, emphasis were on annular flow behavior, phase distribution and liquid film thickness. Liquid film thickness was observed to be thicker mostly when the superficial gas velocities were within 8.2699 m/s to 12.0675 m/s. Above the aforementioned superficial gas velocities, the flow became uniformly distributed on the walls of the internal pipe diameter hence reducing the thicker liquid film at the bottom with gas core at the center of the pipe. More so, annular-slug flow was discovered in the investigation. At superficial liquid velocity of 0.0505 m/s-0.1355 m/s on superficial gas velocities of 8.2699 m/s – 12.0675 m/s, annular-slug flow was prominent. Also discovered was at superficial liquid velocities of 0.0903 m/s - 0.1355 m/s with respect to superficial gas velocities of 13.1692 m/s – 23.4575 m/s, the pipe walls are fully covered with liquid film at very high speed at the entire walls (upper walls and bottom). Also discovered in this experiment is the wavy flow of the upper walls. The liquid film thickness that flows at the upper pipe walls, creeps in a wavy flow. Therefore, the entire flow behavior in an annular flow could be grouped into; wavy-flow at the upper walls, annular-slug flow and thicker liquid film at the bottom with gas core at the center.